A Study on Spatial-Temporal Load Balancing Approach in Cloud Computing - Dhanalakshmi, V. Geetha; Jayasimman, L (International Journal of Computer Sciences and Engineering, 2025)
The main aim of this research paper is to study the spatial-temporal load balancing method and its efficiency of load balancing in cloud computing environment. This paper discusses the methods such as the singular structure and algorithms for unified spatial and temporal load balancing. A novel spatial-temporal load balancing approach that exploits both the geographic and temporal variant of power rate to cope with this trouble. To our best understanding, that is the primary strategy that takes a systematic, unified spatial and temporal load scheduling method in this topic.Rigorous evaluation and tremendous reviews based totally on actuallife statistics exhibit that the proposed spatial-temporal load balancing method can substantially schedule work and assure a provider of completion time for person requests